2015
DOI: 10.1186/s13104-015-1433-0
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Autism Spectrum Disorder (ASD) symptoms and knowledge about some other aspects of ASD among final year medical students in Nigeria, Sub-Saharan Africa

Abstract: Background Earlier studies suggest that knowledge about Autism Spectrum Disorder (ASD) among healthcare workers in Nigeria is low. This present study assessed the knowledge of Nigerian final year medical students about symptoms of ASD and some other aspects of ASD. This is a cross sectional descriptive study that drew a total of seven hundred and fifty-seven (757) final year medical students from ten (10) randomly selected fully accredited medical schools out of a total of twenty-seven (27) fully accredited me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 12 publications
1
20
0
1
Order By: Relevance
“…In our study, the mean score for Domain 1 was determined as 7.07; for Domain 2, 0.89; for Domain 3, 2.69; and for Domain 4, 3.16. In other studies, the average score for Domain 1 ranged between 5.24 and 6.71; for Domain 2, between 0.63 and 0.94; for Domain 3, between 1.1 and 2.62; and for Domain 4, between 1.3 and 3.53 [12][13][14][29][30][31]. According to these results, we conclude that the score obtained from Domains 1 and 3 increased the total mean score in our study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In our study, the mean score for Domain 1 was determined as 7.07; for Domain 2, 0.89; for Domain 3, 2.69; and for Domain 4, 3.16. In other studies, the average score for Domain 1 ranged between 5.24 and 6.71; for Domain 2, between 0.63 and 0.94; for Domain 3, between 1.1 and 2.62; and for Domain 4, between 1.3 and 3.53 [12][13][14][29][30][31]. According to these results, we conclude that the score obtained from Domains 1 and 3 increased the total mean score in our study.…”
Section: Discussionsupporting
confidence: 77%
“…They have determined that mean scores received by psychiatry and paediatric nurses from the questionnaire were close to each other and high [12]. It was determined that senior year medicine students who have attended to the evaluation process of patients with ASD have received higher scores in KCAHW questionnaire Domains 1, 2, 3, and 4 compared to students who have not attended this process, and that there was a statistically significant difference between the groups for each domain [31].…”
Section: Discussionmentioning
confidence: 98%
“…Two studies found those with previous experience working with children with ASD had greater ASD knowledge relative to the group [Bakare, Ebigbo, et al, 2009]. Similar observations were made with medical professionals and health and life sciences students [Bakare et al, ; Eseigbe et al, ; Igwe, Bakare, Agomoh, Onyeama, & Okonkwo, ].…”
Section: Professional Knowledgementioning
confidence: 65%
“…For instance, most of the healthcare workers in Enugu, Nigeria, had limited knowledge of ASD and perceived the quality of healthcare provided to families of children with ASD as suboptimal [50, 51]. Most of the studies on awareness were carried out in Nigeria by Bakare and colleagues [33, 48, 50, 51]. One South African study observed that there were relatively few barriers to participating in ASD research and suggested that most of these barriers were poverty-related [42].…”
Section: Resultsmentioning
confidence: 99%